2011
DOI: 10.1007/s10072-011-0617-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent association between cigarette smoking on white matter hyperintensities

Abstract: Previous reports have shown that cigarette smoking is associated with white matter hyperintensities (WMHs). However, it remains unclear whether this is true for all ages. We investigated the association between cigarette smoking, WMHs, and age. We retrospectively reviewed charts from 595 patients, who presented as outpatients from January 2007 to March 2010. Grading of periventricular WMHs (PVWMHs) and the scores of deep WMHs (DWMHs) was determined based on criteria established by the Rotterdam Scan Study. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
15
2
Order By: Relevance
“…Short-term tobacco smoking is associated with elevation in FA (57, 58), while long-term smoking leads to decline in FA (59, 60). We re-analyzed our data only in non-smoker SCZ vs. non-smoker controls, and found that SCZ patients still experienced higher rates of age-related decline than normal controls (β age*scz = −0.0015±0.0006, t=1.8; p=0.06).…”
Section: Discussionmentioning
confidence: 97%
“…Short-term tobacco smoking is associated with elevation in FA (57, 58), while long-term smoking leads to decline in FA (59, 60). We re-analyzed our data only in non-smoker SCZ vs. non-smoker controls, and found that SCZ patients still experienced higher rates of age-related decline than normal controls (β age*scz = −0.0015±0.0006, t=1.8; p=0.06).…”
Section: Discussionmentioning
confidence: 97%
“…Cerebrovascular risk factors are associated with development of cerebrovascular changes, which increases with increasing age. An age-dependent association between smoking and white matter hyperintensities is found [33]. Our patients population is relatively young, something which may explain the lack of association between cognitive impairment and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Ascertainment of a large antipsychotic-naive SZ patient group is important, across different ages, to rule out interactions between medication effects and aging. Smoking is another possible contributing or confounding factor, because long-term smoking leads to decline in FA (Gons, et al 2011; Kim, et al 2010). Here, we observed no significant mega-analytical effect of smoking status on the whole-brain average FA values.…”
Section: Discussionmentioning
confidence: 99%